Weak memory for future-oriented feedback: investigating the roles of attention and improvement focus. Issue 2 (7th February 2020) - Gregory, Samantha E. A.; Winstone, Naomi E.; Ridout, Nathan; Nash, Robert A.
ABSTRACT: Recent research showed that people recall past-oriented, evaluative feedback more fully and accurately than future-oriented, directive feedback. Here we investigated whether these memory biases arise from preferential attention toward evaluative feedback during encoding. We also attempted to counter the biases via manipulations intended to focus participants on improvement. Participants received bogus evaluative and directive feedback on their writing. Before reading the feedback, some participants set goals for improvement (experiments 1 and 2), or they wrote about their past or future use of the writing skills, and/or were incentivised to improve (experiment 3); we objectively measured participants' attention during feedback reading using eyetracking. Finally, all participants completed a recall test. We successfully replicated the preferential remembering of evaluative feedback, but found little support for an attentional explanation. Goal-setting reduced participants' tendency to reproduce feedback in an evaluative style, but not their preferential remembering of evaluative feedback. Neither orienting participants toward their past or future use of the writing skills, nor incentivising them to improve, influenced their attention toward or memory for the feedback. These findings advance the search for a mechanism to explain people's weaker memory for future-oriented feedback, demonstrating that attentional and improvement-oriented accounts cannot adequately explain the effect.